Análisis cefalométrico lateral integrado, según edad y sexo, de pacientes entre los 6 y los 14 años de edad - Bernal-de Jaramillo, Lucía Victoria (Revista Facultad de Odontología Universidad de Antioquia, 2015)
Standard measurements are applied to all patients in most of the available cephalometric analysis, even though there is a great diversity on the measurements due to age and gender. It is important to note that most of the studies in this area have been performed on adult subjects. Tables included in this article provide linear measurements of various parts of the craniofacial skeleton of boys and girls with ages between 6 and 14. There are also angular measurements that relate some of these parts to others. The object of this research is to facilitate the lateral cephalometric analysis of patients by making the process more organized and complete. The process will then allow a more accurate diagnosis with a more appropriate treatment for each patient.